Nutrient adequacy and environmental foot-print of Mediterranean, pesco-, ovo-lacto-, and vegan menus: a modelling study - Alcalá-Santiago, Ángela; Rodríguez-Martín, Noelia M.; Casas-Albertos, Eduardo; Gálvez-Navas, José María; Castelló-Pastor, Adela; García-Villanova, Belén; Molina-Montes, Esther (Frontiers in Nutrition, 2025)
BackgroundConsumer food choices are changing towards a more plant-based diet (PBD) due to growing awareness of their less detrimental effects on health and the environment. However, PBDs—particularly vegan diets—may lead to nutritional deficiencies compared to non-PBDs. These differences may, in part, be influenced by the typically lower caloric content of PBDs.ObjectiveTo compare the nutritional adequacy and environmental footprints of four 7-day menu models (~ 2,000 kcal/day) Mediterranean (omnivorous) diet, two vegetarian-like diets, and one vegan.MethodsMenus were designed based on the recommendations of the Spanish Society for Community Nutrition (SENC) and Vegetarian Union (UVE), substituting animal-based foods with plant-based alternatives. Nutritional intake was assessed using the Spanish BEDCA food composition table (Base de Datos Española de Composición de Alimentos) and adequacy was evaluated using Dietary Reference Intakes (DRIs) and recommended intake levels. Daily environmental footprints were estimated with Agribalyse. Differences between the four diet models were evaluated by one-way ANOVA or Kruskal-Wallis tests, followed by post-hoc analyses to identify pairwise differences in nutrient intake (significance level: 95%).ResultsDaily macronutrient intake did not differ substantially across the diet groups. Furthermore, all four menus met protein needs and most micronutrient DRIs. Shortfalls were observed for vitamin D and iodine across all diets, and for vitamin B₁₂ in the vegan model; ω-3 PUFA were below the 250 mg/day target in all diets, while saturated fat remained < 8% of total energy intake. Mean daily environmental footprints decreased progressively from omnivorous to vegan diets: −46% CO₂, −6.6% deprived water and −33% land use among others.ConclusionWell-planned PBDs can achieve comparable sustainability and nutritional adequacy to a healthy Mediterranean diet, although attention is required to ensure adequate intake of certain micronutrients.